2010
DOI: 10.1111/j.1365-2109.2010.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damages by cadmium and the protective effects of low-molecular-weight chitosan in the freshwater crab (Sinopotamon yangtsekiense Bott 1967)

Abstract: Cadmium (Cd) is an environmental pollutant and has posed a potential threat for the growth and survival of freshwater crabs. Low-molecular-weight chitosan (LMWC) may promote growth in crab culture. The present study was designed to investigate the Cd-induced oxidative damage and the protective role of LMWC against oxidation caused by Cd 21 in freshwater crab (Sinopotamon yangtsekiense Bott 1967). The results showed that Cd 21 signi¢cantly inhibited the activities of total antioxidant capacity, superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…However, few data are available regarding the effects of exposure to cyanobacterial neurotoxins or PSPs on ROS and T-AOC in fish gills. The current study demonstrated that aphantoxins or PSPs trigger elevations in ROS and reductions in T-AOC levels in the zebrafish gill, suggesting that these toxins induce oxidative stress by increasing the production of free radicals and decreasing the synthesis and/or increasing the use of antioxidants, which is in agreement with previous research (Li et al, , 2011.…”
Section: Changes In Ros and T-aoc In The Gills Of Aphantoxin-exposed supporting
confidence: 93%
“…However, few data are available regarding the effects of exposure to cyanobacterial neurotoxins or PSPs on ROS and T-AOC in fish gills. The current study demonstrated that aphantoxins or PSPs trigger elevations in ROS and reductions in T-AOC levels in the zebrafish gill, suggesting that these toxins induce oxidative stress by increasing the production of free radicals and decreasing the synthesis and/or increasing the use of antioxidants, which is in agreement with previous research (Li et al, , 2011.…”
Section: Changes In Ros and T-aoc In The Gills Of Aphantoxin-exposed supporting
confidence: 93%
“…Thus, more and more LMWCs are used as antioxidant agents. For example, LMWCs are utilized in the preservation of crab and Kamaboko gels and the preparation of edible antioxidant film [ 64 67 ]. In this study, the hydrolysate products of chitosan derivatives, named EG-LMWC, CM-LMWC and AE-LMWC, exhibited significant free radical scavenging activities, and the free radical scavenging activities of those chitosan derivatives were greater than commercial COS. CM-LMWC and AE-LMWC showed superior activity towards ABTS ․+ and peroxyl free radicals compared to EG-LMWC.…”
Section: Discussionmentioning
confidence: 99%
“…Cd ions may induce the accumulation of reactive oxygen species (ROS) [22] which can lead to lipid peroxidation of membrane [23] and is harmful to the mitochondria [24]. Not only mitochondria are the site of energy production, but their roles in the regulation of apoptosis have been accepted [25].…”
Section: Introductionmentioning
confidence: 99%